Legal Protection for Midwives in Performing Medical Services Outside Their Authority: A Normative Juridical Analysis - Wayan Putu Sinarwati; Ida Bagus Surya Darma Jaya (Indonesian Journal of Global Health Research, 2026)
Legal protection for midwives in healthcare practices, particularly in emergency situations, is a crucial issue in Indonesia's healthcare legal system. Although various regulations, such as Law Number 4 of 2019 concerning Midwifery, Law Number 17 of 2023 concerning Health, and Government Regulation Number 28 of 2024, regulate the authority and legal protection of healthcare workers, these regulations are still general in nature and do not provide operational clarity in emergency situations. This study aims to analyze the legal norms regarding midwives' authority and the forms of legal protection they provide for performing medical procedures outside of their formal authority, particularly in emergency situations. The research method used is normative juridical with a statutory and conceptual approach, through an analysis of Law Number 4 of 2019 concerning Midwifery, Law Number 17 of 2023 concerning Health, and Government Regulation Number 28 of 2024. The analysis was conducted qualitatively by interpreting existing legal norms to identify legal gaps related to the legal protection of midwives in emergency situations. The results of the study indicate that normatively, legal protection for midwives has been regulated, but the regulations are still general and do not provide operational clarity regarding medical actions in emergency conditions. This gives rise to multiple interpretations of norms and has the potential to create legal uncertainty in practice. Thus, it is necessary to strengthen more specific and operational regulations to ensure legal certainty and optimal legal protection for midwives.